The Challenges of Physical Special Allocation Fund (SAF) Planning for Sustainable Economic Infrastructure Provision - Andi Setyo Pambudi (The Journal of Indonesia Sustainable Development Planning, 2022)
The paper aimed to examine the relationship between central and regional plan documents, the relevance of the Physical SAF menu to regional development, and how relevant the Physical SAF menu was to the Thematic Assignment of Sustainable Economic Infrastructure Provision (SEIP) to support regional priorities. A quantitative method was used for the analysis. It was carried out in a desk study with content analysis to track the 2021 Physical SAF policy for the assignment of SEIP in the Government Work Plan (GWP) and regional priorities of the Provincial Government Work Plan (PGWP). The results of the planning level analysis showed that there are still some irrelevant Physical SAF policies to the regional priorities for the themes of Tourism, Roads, Small and Medium Industries (SMEs), and the Environment. There are still many plans and activities for the Physical SAF not included in the provincial government's planning, thus affecting the implementation quality.